Enteroaggregative Escherichia coli foodborne outbreak in Shandong Province, China (2023): comprehensive epidemiology and genomic resistance profiling - Liu, Lu; Wang, Shuang; Yu, Xiaolin; Chen, Yuzhen; Chen, Yanru; Sun, Gaoxiang; Liu, Ziqing; Cheng, Lixiao; Zhang, Huaning; Kou, Zengqiang (Frontiers in Microbiology, 2025)
IntroductionEnteroaggregative Escherichia coli (EAEC) is an emerging and intricate diarrheagenic bacterial pathogen responsible for acute and persistent diarrhea in children, adults, and travelers. Despite its clinical significance, the global understanding of EAEC outbreaks and pathogen characteristics remains limited due to its complex epidemiological profile.MethodsThis study presented a retrospective analysis of a foodborne diarrheal outbreak caused by EAEC in a county school in Shandong Province, China in 2023 by using epidemiological investigation and comprehensive genomic analysis techniques.ResultsA total of 15 EAEC isolates were identified, including 13 from stool samples, one from sauced beef, and one from flies. Epidemiological and phylogenetic analyses pinpointed the EAEC isolates from sauced beef as the primary causative agent of the outbreak. Genomic comparisons revealed significant genetic consistency across nine outbreak-associated strains, particularly in virulence gene profiles, antimicrobial resistance gene profiles, molecular typing, and genetic evolution.DiscussionThese findings underscored the utility of whole-genome sequencing in elucidating the genetic diversity of EAEC within specific environments and tracing its origins, thereby supporting targeted interventions such as infection control and prevention strategies. Notably, the study also identified an extensively drug-resistant (XDR) EAEC strain from flies in the canteen, harboring both the mcr-1 and blaCTX-M-132 resistance genes. This unexpected discovery highlighted the critical importance of applying the “One Health” approach, emphasizing the need for continuous surveillance of antibiotic-resistant bacteria in animals and environmental sources to mitigate potential public health risks.